Efeito de diferentes herbicidas, doses e volume de calda na dessecação de milheto [Pennisetum glaucum (L. Leek)] - Campos, Caio Ferraz de [UNESP]; Martins, Dagoberto [UNESP]; Rodrigues, Andreia C. P.; Cardoso, Leonildo Alves [UNESP]; Cardoso, José Iram [UNESP]; Cosa, Neomarcio Villanova da (My University, 2011)
The objective of this work was to evaluate the efficacy of different herbicides applied in post-emergence in the desiccation of pearl millet with different doses and spray volumes. For the desiccation, doses at 0, 25, 50 and 100% of the herbicide glyphosate (1,440 g ha-1) were used in 3 formulations (Original Round up, Round up Transorb and Round up WG), paraquat + diuron (500 + 250 g ha-1) and glufosinateammonium (800 g ha-1). In all treatments, 2 spray volumes (200 and 400 l ha-1) were used, and there was 1 treatment (control) without the application of herbicides. The treatment effects were evaluated visually at 3, 7, 14, 21 and 28 days after application (DAA). At the end of the evaluations, the dry mass of the plants was determined. The field trial was carried out in randomized block design. At the end of the study, at 28 DAA, all treatments presented total control of plant pearl millet, regardless of the dose and spray volume, except the treatments with paraquat + diuron and glufosinate-ammonium at the lower dose (25%), in 2 spray volumes, which nevertheless showed good and very good control, these two herbicides presenting an effect of volume, in which the control was higher with the use of smaller volume.

Objetivou-se nesse trabalho avaliar a eficácia de diferentes herbicidas aplicados em pósemergência na de secação do milheto com diferentes doses e volumes de calda de aplicação. Para a dessecação do milheto foram utilizadas doses de 0, 25, 50 e 100% dos herbicidas glyphosate (1.440 g ha-1), em três formulações comerciais (Round up Original, Round up Transorb e Round up WG), paraquat + diuron (500 + 250 g ha-1) e amônio-glufosinato (800 g ha-1). Em todos os tratamentos foram utilizados dois volumes de aplicação (200 e 400 L ha-1). Manteve-se uma testemunha sem aplicação de herbicidas. Os efeitos dos tratamentos foram avaliados visualmente aos 3, 7, 14, 21 e 28 dias após aplicação. Ao final das avaliações foi determinada a massa seca das plantas. O estudo de campo foi instalado no delineamento em blocos casualizados. No final do estudo, aos 28 DAA, todos os tratamentos apresentaram controle total das plantas de milheto, independente da dose e do volume de aplicação, exceto para os tratamentos com paraquat + diuron e amônio-glufosinate na menor dose (25% da dose), nos dois volumes de aplicação, que apresentaram ainda controles considerados bons a muito bom, sendo que para esses dois herbicidas houve efeito do volume de calda, na qual o controle foi superior com o uso de volume menor.
Effect of different herbicides, doses and spray volume in the chemical management of pearl millet [Pennisetum glaucum (L. Leek)]
Keywords: Herbicide; Spraying technology; No-tillage; Herbicida; Tecnologia de aplicação; Plantio direto